SN 2017ckj: A linearly declining type IIb supernova with a relatively massive hydrogen envelope - Li, L. H.; Benetti, S.; Cai, Y. -Z.; Wang, B.; Pastorello, A.; Elias-Rosa, N.; Reguitti, A.; Borsato, L.; Cappellaro, E.; Fiore, A.; Fraser, M.; Gromadzki, M.; et al. (EDP Sciences, 2026)
We present optical observations of the type IIb supernova (SN) 2017ckj, covering approximately 180 days after the explosion. Its early-time multi-band light curves display no clear evidence of a shock-cooling tail, resembling the behaviour of SN 2008ax. The V-band light curve exhibits a short rise time of about 5 days and reaches an absolute fitted peak magnitude of MV = -18.49 +/- 0.18 mag. The late-time multi-band light curves reveal a linear decline. We modelled the bolometric light curve of SN 2017ckj to constrain the progenitor and the explosion parameters. We estimated a total mass of Ni-56 synthesised by SN 2017ckj of M-Ni = 0.21(-0.03)(+0.05) M-circle dot, with a massive H-rich envelope of M-env = 0.4(-0.1)(+0.1) M-circle dot. Both the Ni-56 mass and the envelope mass of SN 2017ckj are higher than those of typical SNe IIb, in agreement with its peculiar light curve evolution. The early-time spectra of SN 2017ckj are dominated by a blue continuum, accompanied by narrow H alpha and He II emission lines. The earliest spectrum exhibits flash ionisation features, from which we estimated a progenitor mass-loss rate of similar to 3 x 10(-4) M-circle dot yr(-1). At later epochs, the spectra develop broad P-Cygni profiles and become increasingly similar to those of SNe IIb, especially SN 2018gk. The late-time spectrum at around 139 days does not show a distinct decline in the strength of its H alpha emission profile, also indicating a relatively massive envelope of its progenitor. Aside from the H alpha feature, the nebular spectrum exhibits prominent emission lines of O I, Ca II, [Ca II], and Mg I], which are consistent with the prototypical SN 1993J.